Kewirausahaan bagi Peningkatan Ekonomi Jemaat di Jemaat Kristen Indonesia Tongkat Kerajaan Salatiga - Yonius Zalukhu (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
Entrepreneurship try to reach welfare economy of citizen constitute a responsibility of church's institution in creating a better life. Covid 19 Pandemic has given impact in economic bussiness where the strategy used by UMKM actors in agrobussiness to increase and mantain their income. The success of UMKM can bring Economic Improvement. Reseach method is qualitative descriptive with research instruments such as indepth interview, observation, and documentation. the result of shows (a) a couple of obstacles such as nature obstacle, human obstacle, and economic obstacle (capital). the word of the Lord regarding entrepreneurship i.e about trust to the blessing source, about running the daily bussiness, about sugestion to do online selling, etc. marketing be utilized such as wrapping, online opportunity, announcement utilization, online shop shopee, application whatsapp, (d) process open new branch (e) selling in facebook application (f) joining bazar (g) inspiration from the shepherd with online selling such as facebook, Tiktok, Go Food, Shopee, and grab (h) door to door selling (i) about customer. Solution and testimony divided into: spiritual solution and bodily solution. Testimony: The Lord bless with house and blessing for the children of the Lord; blessing buying rice with uncoincidently found in the street. The Lord bless therefore still able to harvest, be multiplied in harvest's result and the Lord send the buyers.